COMPARATIVE TOXICITY AND RISK ASSESSMENT OF SOME PESTICIDES ON THE PARASITOID, Habrobracon hebetor (Say) (Applied Biological Research, 2025)
Habrobracon hebetor (Say) is a widely used gregarious ectoparasitoid in biological control programs targeting lepidopteran pests. However, the extensive use of chemical pesticides poses potential risks to such beneficial organisms. This study evaluated the lethal and sublethal effects of four commonly used pesticides—imidacloprid, acephate, propiconazole, and fenoxaprop-p-ethyl—on adult H. hebetor using concentration–mortality assays and risk quotient (RQ) analysis. Among the tested compounds, acephate was the most toxic, with LC₅, LC₃₀, and LC₅₀ values of 0.01, 0.15, and 0.52 mg L⁻¹, respectively, and an RQ value of 1442.31, indicating a high ecological risk. In contrast, imidacloprid exhibited LC₅, LC₃₀, and LC₅₀ values of 0.27, 8.27, and 40.75 mg L⁻¹, respectively, with an RQ of 0.61, suggesting minimal risk. The fungicide propiconazole (LC₅₀: 23.79 mg L⁻¹; RQ: 5.25) and the herbicide fenoxaprop-p-ethyl (LC₅₀: 995.41 mg L⁻¹; RQ: 0.06) also showed low toxicity, with sublethal concentrations well above field-relevant levels. These findings highlight the need to integrate both lethal and sublethal toxicity endpoints when assessing pesticide compatibility with natural enemies. Future research should examine long-term sublethal impacts on reproductive, behavioural, and molecular traits to enhance sustainable integrated pest management (IPM) strategies.
Keywords: Bioassay; biological control; hazard quotient; natural enemy; risk assessment